Acromioclavicular joint dislocation: a comparative biomechanical study of the palmaris-longus tendon graft reconstruction with other augmentative methods in cadaveric models. - Luis, G.E.; Yong, C.K.; Singh, Deepak A; Sengupta, S.; Choon, David Sk (BioMed Central, 2007)
Modified Weaver-Dunn procedure must always be supplemented with acromioclavicular capsuloligamentous repair to increase posterior-anterior stability. Palmaris-Longus tendon graft provides both additional superior and posterior-anterior stability when used for acromioclavicular capsuloligamentous reconstruction. It is a good alternative to clavicle hook plate in acromioclavicular dislocation.